HUBUNGAN KELINCAHAN DAN KECEPATAN DENGAN KETERAMPILAN MENGGIRING BOLA PADA TIM SEPAK BOLA SMKN 5 PEKANBARU - Agust, Kristi Agust Kristi; ', M.tarmizi M.tarmizi; ', Ramadi Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is whether there is a relationship of the agility and speed with dribbling ball skill. The goal is to find out how big relationship agility and speed with dribbling ball skill the unity of football athlete throughout SMKN 5 Pekanbaru. The technique of sampling performed with total sampling of 18 football athlete SMKN 5 Pekanbaru. This study using a correlation technique. Then, the data are tested using the test of normality, test the product moment correlation test, test of significance on the level of significance of α = 0.05. Test of normality of variabels X1, L0maks 0,171 < Ltabel or 0,200, variabel X2, L0maks 0,199 < Ltabel or 0,200 and testing normality of variabels Y, L0maks 0,188 < Ltabel or 0,200 in other words at a confidence level of 95% of normal data and concluded the results showed: First, there is a significant relationship between agility with dribbling ball skill, and correlation r1= 0,525, where rhitung > rtabel or 0,468. Second, there is a significant relationship between speed with dribbling ball skill, and correlation r2= 0.490, where rhitung > rtabel or 0.490 > 0,468. Third, there is a significant relationship between agility and speed with dribbling ball skill, with R= 0,587 which obtained Rhitung= 0.587 and rtabel= 0.468 it means Rhitung > rtabel, Ho rejected and Ha accepted.Key word: Agility, Speed And Dribbling Ball Skill.